Third Order Intermodulation Distortion Effect on The Constellation Error in RF Transmitter of IEEE 802.11a WLAN System - Noor Azwan, Shairi; Imran, Mohd Ibrahim (IEEE, 2011)
In wireless data communication, an advanced nonlinear distortion analysis is required in order to see its effect to the performance of a Radio Frequency (RF) front-end system. This technical paper therefore, reports the effect of third order intermodulation (IM3) distortion on the constellation error (a key measure of modulation quality) in RF transmitter of IEEE 802.11a wireless local area network (WLAN) system. The selected RF transmitter architecture is based on the off-the-shelf components. Advanced Design System (ADS) software has been used for RF transmitter modeling and simulation. The constellation error simulation is based on the IEEE 802.11a standard. As results, two observations have been obtained. First, it is shown that the IM3 distortion in the RF transmitter for IEEE 802.11a WLAN system must be kept in minimum level in order to get lower constellation error. Second, with the same IM3 distortion level, the constellation error is very sensitive to the IM3 distortion at higher data rate (e.g. 54 Mbps) compared to lower data rate (e.g. 6 Mbps).